2002
DOI: 10.1021/la025604q
|View full text |Cite
|
Sign up to set email alerts
|

Forces between Polystyrene Particles in Water Using the AFM:  Pull-Off Force vs Particle Size

Abstract: Adhesion between polystyrene particles in high purity water has been measured for a wide range of particle sizes. The results are compared with predictions based on the JKR model using literature values of the solid-vapor surface energy. When the surface roughness of the particles is accounted for, the JKR adhesion is still too large. An optimum value of the surface energy is calculated for one tip particle size and used for predicting the pull-off force for all of the substrate particle sizes, and it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 29 publications
7
43
0
Order By: Relevance
“…Obtained floc strength was 2 nN in average and did not depend on floc size. The values of floc strength of this study were also compared with those of previous studies [11,13,14,17,18].…”
Section: Introductionmentioning
confidence: 89%
“…Obtained floc strength was 2 nN in average and did not depend on floc size. The values of floc strength of this study were also compared with those of previous studies [11,13,14,17,18].…”
Section: Introductionmentioning
confidence: 89%
“…13,14 The modeling of pull-off force is mainly based on two different approaches based on the surface energies on the contact, [15][16][17][18] or on the integration of the van der Waals forces between objects [19][20][21][22] and on some hybrid approaches between both. 23,24 The adhesion force reduction was already obtained in liquid and dry medium by surface structuring [24][25][26] or chemical functionalisation. 9,[27][28][29] The last technique allows to switch the force from attractive to repulsive by pH solution modification and improves the micro-object manipulation.…”
mentioning
confidence: 99%
“…It has been reported that the attractive force of a polystyrene particle with a solid surface and the force between silica particles covered with CTAB layers could be measured by AFM. [22][23][24][25] In comparison with AFM method, which has the sensitivity of 0.1 nN, our method proved to have a higher sensitivity, of pN order, in the measurement of adsorption force. DLVO theory explained the interaction force between two surfaces as the combination of van der Waals force and the electrostatic repulsion force.…”
Section: Resultsmentioning
confidence: 89%